Effects of feeds on selected shellfish (Macrobrachium rosenbergii) and finfishes (Planiliza persia and Rhinomugil corsula) in polyculture system: profitability and viability - Akter, Mafia; Suravi, Israt Nur; Islam, Md Shahidul (Journal of the Asiatic Society of Bangladesh, Science, 2023)
The experiment was conducted at earthen ponds in the Bagerhat sadar upazila of Bagerhat to examine the growth, production capacity, and economic return of freshwater prawn (Macrobrachium rosenbergii) with persa (Planiliza persia) and corsula mullet (Rhinomugil corsula) under polyculture system. Four treatments, designated as T1, T2, T3, and T4 were used in the study, each with three replicates. The final weight of the prawns after 120 days of culture was highest in T1 (72.07 g) and lowest in T4 (50.23 g), but there was no significant difference in prawn growth between T1 and T2. In T4, where artificial feed was not employed, prawn, persa, and corsula mullet growth and survival rates were lower. T1 produced more prawns (173.27 kg ha-1), while T4 produced less (617.83 kg ha- 1). Significantly (p<0.05) higher production of persa was found in T1 (295.97 kg ha-1) and lower in T4 (152.28 kg ha-1). Corsula production was also observed to be higher in T1 (275.70 kg ha-1) and lower in T4 (155.36 kg ha-1). However, T1 had much higher total production and net profit from prawn and fish farming (1744.94 kg ha-1, BDT 244694.75 ha-1), whereas T4 had a significantly lower total production and net profit (925.46 kg ha-1, BDT 115894.42 ha-1). According to the study, quality feed (T1) outperforms other commercial feeds in terms of growth, production, and net profit. In order to increase productivity and get a high return on investment in a short period of time. The quality feed can be recommended. J. Asiat. Soc. Bangladesh, Sci. 48(1-2): 111-122, June-December 2022